Acute acalculous cholecystitis in an infant after gastroschisis closure. Issue 2 (4th March 2023) - Shehzad, Irfan; Nelson, Nicholas; Vora, Niraj; Wills, Hale; Birkemeier, Krista; Govande, Vinayak
Abstract: Gastroschisis is a common type of congenital anterior abdominal wall defect with intraabdominal organs exposed outside the abdominal cavity. With modern neonatology and surgical practices, the overall prognosis for infants with gastroschisis is excellent. However, a subset of infants with gastroschisis will develop complications, requiring repeat surgical interventions. We present a case of a female infant with complicated gastroschisis who developed acute perforated acalculous cholecystitis, which was accurately diagnosed with abdominal ultrasound and successfully treated with medical management and a percutaneous cholecystostomy tube.